Risk factors for endemic giardiasis - association with contaminated water and food - Surin, J.; Mahdy, M.A.; Lim, Y.A.; Al-Mekhlafi, H.M. (2008)
This study was conducted to reassess the risk factors for giardiasis in communities of the Orang Asli (indigenous people) in Pahang, Malaysia. Stool samples were collected from 321 individuals (2-76 years old; 160 males, 161 females). Data were collected via laboratory analysis of faecal samples and a pre-tested standard questionnaire. River water samples were tested for Giardia cysts and Cryptosporidium oocysts. The overall prevalence of G. intestinalis infection was 23.7. Children 12 years old had the highest infection rate and have been identified as a high risk group (odds ratio (OR) = 6.2, 95 CI 1.5-27.0, P < 0.005). The risk of getting giardiasis also appeared to be significantly associated with drinking piped water (OR = 5.1, 95 CI 0.06-0.7, P < 0.005) and eating raw vegetables (OR = 2.4, 95 CI 0.2-0.6, P < 0.005). In conclusion, sociodemographic factors have always been associated with the high prevalence of Giardia infections in Malaysia. However, the present study also highlights the need to look into the possibility of other risks such as water and food transmission routes. In future, it is necessary that these two aspects be considered in control strategies.